Analisis Penerapan dan Efektivitas Sistem Imprest dalam Pengelolaan Kas Kecil pada UMKM Nasi Goreng Semolowaru Surabaya - Aprilia Tri Kurniawati; Sunarti Sunarti; Sri Rahayuningsih (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the implementation and effectiveness of the imprest system in managing petty cash in a small-scale culinary microbusiness, Nasi Goreng Semolowaru Surabaya. This study uses a qualitative descriptive method with a case study approach. Data were collected through observation, interviews, and documentation of daily operational and financial recording activities. The results show that the implementation of the imprest system has helped maintain order in the use of petty cash and improved transaction recording discipline. Every operational expenditure, such as the purchase of raw materials, gas, and spices, is documented with a simple receipt before replenishing the petty cash. However, the effectiveness of this system is still limited due to inconsistent replenishment practices and the mixing of personal and business money. Overall, the imprest system plays an important role in improving financial transparency and control, although ongoing guidance is needed to strengthen financial management awareness among microentrepreneurs.